How cohesive are you in virtual communities? - Sahharon, Hamizah; Bolong, Jusang; Omar, Siti Zobidah; Idris, Khairuddin (Human Resource Management Academic Research Society, 2020)
Although a cohesive society is difficult to maintain, social cohesion is seen as ideal to unite a heterogeneous community. Studies in the past have focused on social cohesion within real life context involving face-to-face encounters, nowadays it was noted that social networking sites (SNS) have a role in determining the level of social cohesion. This study aims to examine the role of SNS in determining the level of social cohesiveness among its virtual youth communities’ members. A total of 600 multiethnic youths in urban and rural areas in Malaysia were selected based on a multi-stage cluster sampling technique. The respondents were asked to state their level of agreement on sense of togetherness, sense of belonging, social trust, and social interaction through a distributed self-administered questionnaire. The results showed that the overall level of social cohesion among virtual youth communities was only moderate and the dimension sense of belonging yielded the highest score. This study implied that SNS are capable of enhancing the level of social cohesion among youths in Malaysia.